Revised approach to the role of fatigue in anterior cruciate ligament injury prevention: A systematic review with meta-analyses - Benjaminse, A.; Webster, K. E.; Kimp, A.; Meijer, M.; Gokeler, A. (Sports Medicine, 2019)
Background: Causes of anterior cruciate ligament (ACL) injuries are multifactorial. Anterior cruciate ligament injury prevention should thus be approached from a multifactorial perspective as well. Training to resist fatigue is an underestimated aspect of prevention programs given that the presence of fatigue may play a crucial role in sustaining an ACL injury. Objectives: The primary objective of this literature review was to summarize research findings relating to the kinematic and kinetic effects of fatigue on single-leg landing tasks through a systematic review and meta-analysis. Other objectives were to critically appraise current approaches to examine the effects of fatigue together with elucidating and proposing an optimized approach for measuring the role of fatigue in ACL injury prevention. Methods: A systematic literature search was conducted in the databases PubMed (1978-November 2017), CINAHL (1992-November 2017), and EMBASE (1973-November 2017). The inclusion criteria were: (1) full text, (2) published in English, German, or Dutch, (3) healthy subjects, (4) average age =?18 years, (5) single-leg jump landing task, (6) evaluation of the kinematics and/or kinetics of the lower extremities before and after a fatigue protocol, and (7) presentation of numerical kinematic and/or kinetic data. Participants included healthy subjects who underwent a fatigue protocol and in whom the effects of pre- and post-fatigue on three-dimensional lower extremity kinematic and kinetics were compared. Methods of data collection, patient selection, blinding, prevention of verification bias, and study design were independently assessed. Results: Twenty studies were included, in which four types of single-leg tasks were examined: the single-leg drop vertical jump, the single-leg drop landing, the single-leg hop for distance, and sidestep cutting. Fatigue seemed to mostly affect initial contact (decreased angles post-fatigue) and peak (increased angles post-fatigue) hip and knee flexion. Sagittal plane variables at initial contact were mostly affected under the single-leg hop for distance and sidestep cutting conditions whilst peak angles were affected during the single-leg drop jump. Conclusions: Training to resist fatigue is an underestimated aspect of prevention programs given that the presence of fatigue may play a crucial role in sustaining an ACL injury. Considering the small number of variables affected after fatigue, the question arises whether the same fatigue pathways are affected by the fatigue protocols used in the included laboratory studies as are experienced on the sports field.